Self-Efficacy and Problem-Solving among College Students during COVID-19 Pandemic - F Fatmawati; Siti Maryam (Psyche 165 Journal, 2021)
During the COVID-19 pandemic and the implementation of online learning system, the pressure faced by students is far greater than before. The existence of the problems certainly requires students to be able to survive and find the right way out. Problem-solving is an indication that shows how strong a person is in facing a difficulty. Students with high self-efficacy believe that they are able to do something to change the problems around them. Therefore, this study aimed to measure the association between self-efficacy and problem-solving among college students during COVID-19 pandemic. The number of participant recruited through accidental random technique was 150 college students in the city of Banda Aceh. General Self-Efficacy Scale was employed in order to obtain the data on self-efficacy, whereas problem-solving ability was calculated through Solving Problem Survey. Pearson Correlation was used to analyze the data and it showed a positive relationship between those two variables. Besides, the analysis also displayed a significance value of 0.000 (p<0.05). This indicated that the hypothesis was accepted –there was a very significant relationship between self-efficacy and problem-solving among college students during COVID-19 pandemic.